The Contribution of the Mathematical Patterns Application to the Adoption of Learning Strategies in the Teaching of German as a Foreign Language - Marija M. Stanojević Veselinović (University of Belgrade, Teacher Education Faculty, 2024)
The paper deals with an innovative methodological approach in learning a second foreign language, in this case the German language. The approach has been developed on the basis of the similarity of the system of rules in grammar with mathematical patterns and it is supported by the principles of the theory of Generative Grammar. The goal of the paper is to show the application of mathematical rules in the German language learning, as a way of how these rules can improve the teaching and learning of German as a foreign language. Mathematics as a universal language is related to and corresponds to the definition of language, as mathematics and language require abstract thinking, use logical patterns, and have defined rules. Accordingly, certain similar or the same mathematical rules and patterns were registered in different segments of the language: in vocabulary, semantics, grammar, syntax, and discourse. The established models of patterns significantly contribute to the improvement of teaching and learning German as a foreign language by presenting the ways by which not only the semantic rules of the sentences, but also other grammar rules in a foreign language can be adopted, as well as logical and learning strategies and techniques.